Strategi pemasaran digital sebagai pemberdayaan masyarakat dalam pengembangan Usaha Mikro, Kecil dan Menengah (UMKM) di Kelurahan Air Dingin Kota Pekanbaru - Neni Hermita; M. Yogi Riyantama Isjoni; Zetra Hainul Putra; Mahmud Alpusari; Jesi Alexander Alim; Dahnilsyah Dahnilsyah; Joleha Joleha; Precian Agung Assyafi’I; Hafizt Muhamad Islami; Noval Rivaldo; Novia Yuliana Anita; Nurlaili Suriyani; Ghulami Afra Rulya; Medina Sophie Anggini; Tsani Latifa; Ayu Sulistyaningsih (Unri Conference Series: Community Engagement, 2022)
The term digital marketing is crowded along with the increasing use of the internet. Unlike before the internet, digit activity. As the purpose of this community service activity is as an empowerment to improve understanding, especially marketing of MSME products in Air Dingin Village with a descriptive method of analysis with a qualitative approach. The object of the study is all MSMEs in Cold Water Village, Bukit Raya District, Pekanbaru City. Data collection using the interview method with data analysis techniques using deduction logic, comparing the theories behind the problem. The conclusion obtained that the development of MSME Digital Marketing in Air Dingin Village is able to become a driving factor for regional economic growth and has a positive impact on the progress of MSME.